Comorbidity between eating disorders and anxiety disorders: A review - Godart, N. T.; Flament, M. F.; Perdereau, F.; Jeammet, P. (The International journal of eating disorders, 2002)
Objective We conducted a critical literature review on studies assessing the prevalence of anxiety disorders (AD) in subjects with eating disorders (ED) (anorexia nervosa and bulimia nervosa). In the first part, we discuss methodological issues relevant to comorbidity studies between ED and AD. In the second part, taking into account these methodological considerations raised, we summarize the findings of these studies. Method We performed a manual and computerized search (Medline) for all published studies on comorbidity between ED and AD, limiting our search from 1985–2001 to get sufficiently homogeneous diagnostic criteria for both categories of disorders. Results Too few studies include control groups and few studies have compared diagnostic subgroups of ED subjects, with scarce or conflicting results. Discussion We discuss the results taking into account the methodological problems observed. We give guidelines for reviewing the results of published studies and planing future research. © 2002 by Wiley Periodicals, Inc. Int J Eat Disord 32: 253–270, 2002.